The Effect of Shrimp Pond Solid Waste Utilization on Protein and Chlorophyll Content in Caulerpa lentillifera Cultivation - Muhammad Ikhwan Ihtifazhuddin; Nyoman Robby Manik Saputra; Ramanda Ahmad Rizal Rifa’i; Priatno Khanna (Journal Of Artha Biological Engineering, 2026)
Aquaculture waste is material produced by fish or shrimp farming that can pollute aquatic environments if not promptly managed. The solution to solve this problem is to utilize shrimp pond solid waste as organic fertilizer. The shrimp pond solid waste will be used as fertilizer to cultivate Caulerpa lentillifera. Caulerpa lentillifera cultivation has begun to develop in Indonesia because, in addition to being edible fresh, it also contains good nutrition for the body. This study aims to determine the effect of shrimp pond solid waste on protein and chlorophyll levels of Caulerpa lentillifera. This study was conducted with 4 (four) treatments in the form of different doses of shrimp pond waste (0, 2, 4, and 6 g/L) and 3 (three) replications in each treatment. The parameters tested included nutrient, protein, and chlorophyll content, as well as water quality, in Caulerpa lentillifera cultivation. The results obtained from this study are Caulerpa lentillifera is able to utilize the nutrient content in shrimp pond solid waste as fertilizer to add nutrients. Treatment C had the highest effect with protein content (8.27%) and chlorophyll-a (3.46 mg/g), chlorophyll-b (7.41 mg/g); and total chlorophyll (16.08 mg/g) in Caulerpa lentillifera. Based on these data, it can be seen that shrimp pond solid waste can be used as fertilizer in the cultivation of Caulerpa lentillifera.